Why Most People Disapprove of Me: Experience Sampling in Impression Formation - Denrell, J (2005)
Individuals are typically more likely to continue to interact with people if they have a positive impression of them. This article shows how this sequential sampling feature of impression formation can explain several biases in impression formation. The underlying mechanism is the sample bias generated when the probability of interaction depends on current impressions. Because negative experiences decrease the probability of interaction, negative initial impressions are more stable than positive impressions. Negative initial impressions, however, are more likely to change for individuals who are frequently exposed to others. As a result, systematic differences in interaction patterns, due to social similarity or proximity, will produce systematic differences in impressions. This mechanism suggests an alternative explanation of several regularities in impression formation, including a negativity bias in impressions of outgroup members, systematic differences in performance evaluations, and more positive evaluations of proximate others.